(untitled) (FUDMA JOURNAL OF SCIENCES, 2024)
The evaluation of udder measurement and milk composition of two breeds of sheep were assessed. A total of one hundred and sixty sheep comprising of (80 Yankasa and 80 Uda breeds of sheep. Matured ewes were used, age ranges between 2- 4 years of age and with average body weight of 30 - 40kg.The udder characteristics were measured using flexible tape, vernier caliper, while body weight was measured using weighing balance. Milk qualities were analyzed for fat%, protein % lactose%, solid and non-solid fat% and vitamins %. The body weight (BW), udder length (UL) and udder volume (UV) were significantly affected by breed with Yankasa breed having the higher value of 40.93±2.1 kg, 14.19±0.54cm and 1.31±0.11m3 followed by Uda breed 37.37±1.50 kg, 12.11±0.37cm and 0.95±0.07 m3. Strong positive and significant correlation was recorded between udder width and udder volume (r =0.79**), udder length and udder volume (r =0.78**) while moderate correlation was observed between udder width and udder circumference (r =0.53**). There was significant difference (p<0.05) during lactation in value of udder length 13.70cm, udder weight 12.88kg, udder circumference 4.15cm, udder volume 1.25m3, teat length 2.71cm, teat width 1.67cm and distance between teat to floor 6.53 cm was higher in Yankasa breed than Uda breed. There was significant difference (p<0.05) with Yankasa breed ewes during pregnancy which had higher body weight 42.99kg, higher udder length 14.68cm, udder width 12.49cm, and udder volume 1.37m3 as compared to Uda breed There was significant variations in the shape of the...